AN INVESTIGATION OF EFL STUDENT'S LEARNING STRATEGIES BASED ON GENDER DIFFERENCES ON ONLINE TEACHING AND LEARNING - Nurul Hidayah; Lilia Indriani (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The result of previous studies on English Foreign Language (EFL) learning indicate that the students apply all of the learning strategies as follows; meta-cognitive, cognitive, social, and affective strategies (Safitri, Sumardi, Supriyadi, 2018). Individual differences are the factor that influences the Language learning strategies (LLS) and plays an influential role in the process of language learning. In this regard, this paper makes attempt to explore the online learning strategies used by Indonesian EFL students and to analyze those strategies in performance assessment during online teaching and learning concerning gender differences. This paper applies a qualitative study with a total of 30 EFL learners (15 males and 15 females) selected from the 5th-semester student at Tidar University. The participants completed the questionnaire data that consist of thirteen statements from the previous study (Safitri, Sumardi, Supriyadi, 2018). The researcher finding from this study is female students frequently used more learning strategy rather than males students in online learning.